BERLAKUNYA HUKUM PERIKATAN ISLAM DAN HUKUM NASIONAL DI INDONESIA - Febriansyah, Ferry Irawan (LIPI, 2015)
In the legal engagements within the Unitary Republic of Indonesia emerged two rules governing the engagement according to Islamic law and agreements according to national law. The problem that arises is the enactment of these laws, both engagements according to Islamic law or the law of the engagement according to the National. Analysis study in the discussion that includes the enactment of these laws, namely the engagement according to Islam and agreements according to national law. Islamic law is part of the national legal sources whose role is crucial in shaping national law in Indonesia. Applicability of engagement according to Islamic law, as positive law that is used in making the agreement in line with the rule of law as set out in the agreement of national law. Based on the principle of freedom of contract enunciated in the book III of the Code of Civil Code, then the principle of providing the broadest possible authority to the parties to the agreement in accordance with their wishes and can override the rule of law that serves as a complement.